Pharmacognostical Phytochemical and Pharmacological Review on Bryophyllum pinnata - Prasad, Anuradha K (International Journal of Pharmaceutical & Biological Archive, 2012)
Pharmacognostical Phytochemical and Pharmacological Review on Bryophyllum pinnata